2021
DOI: 10.31219/osf.io/bc2wy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions to reduce meat consumption by appealing to animal welfare: Meta-analysis and evidence-based recommendations

Abstract: Reducing meat consumption may improve human health, curb environmental damage, and limit the large-scale suffering of animals reared in factory farms. Most attention to reducing consumption has focused on restructuring environments where foods are chosen or making health or environmental appeals. However, psychological theory suggests that interventions appealing to animal welfare might operate on distinct, potent pathways. We conducted a systematic review and meta-analysis evaluating the effectiveness of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 92 publications
(134 reference statements)
1
15
0
Order By: Relevance
“…For example, a recent meta-analysis suggested that interventions appealing to animal welfare (e.g. by portraying farm animals) hold promise for reducing meat purchases and consumption (68) . We also did not assess other potentially important aspects of message design, such as message framing (69)(70)(71) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent meta-analysis suggested that interventions appealing to animal welfare (e.g. by portraying farm animals) hold promise for reducing meat purchases and consumption (68) . We also did not assess other potentially important aspects of message design, such as message framing (69)(70)(71) .…”
Section: Discussionmentioning
confidence: 99%
“…25 Multiplicative measures are also sometimes used in contexts when converting studies' estimates to a common, additive scale would invoke potentially unrealistic distributional assumptions, as was the case in the second applied example. 13 Additive measures are often more relevant to assessing interventions' effects on public health, for example when estimating the "number needed to treat" based on a risk difference or when identifying which subgroup to treat based on an additive interaction measure. 26 When assessing public health effectiveness in this sense, then regardless of the scale on which analyses are conducted, the effect measures should be converted to public healthrelevant measures before one considers whether effects are meaningfully strong.…”
Section: Choices Of Effect-size Measuresmentioning
confidence: 99%
“…Mathur et al 13,34 conducted a meta-analysis to assess the effectiveness of educational behavior interventions that attempt to reduce meat consumption by appealing to animal welfare. They meta-analyzed 100 studies (from 34 articles) of such interventions, all of which measured behavioral or self-reported outcomes related to meat consumption, purchase, or related intentions and had a control condition.…”
Section: Behavior Interventions To Reduce Meat Consumptionmentioning
confidence: 99%
See 2 more Smart Citations